SOSIALISASI PEMANFAATAN LIMBAH BATANG SAWIT UNTUK PEMBUATAN GULA MERAH & DAMPAKNYA SEBAGAI USAHA HOME INDUSTRI DI DESA PASAR LAPAN KEC. AIR PUTIH - Suhardi Napid; Oris Krianto Sulaiman; Rahmad Setia Budi; Muji Paramuji; Rachmat Rizaldi; Maulidya Rahmah; Reyhan Reyhan (Jurnal Pengabdian Mitra Masyarakat, 2023)
Processed products of palm sap are cooked for a certain duration of time to produce brown sugar. In general, the community still uses coconut/aren sap water as a raw material for making brown sugar, but currently residents of Pasar Eight village in Air Putih sub-district have made brown sugar using waste palm stems to get the sap water and then mix it with white sugar. The purpose of community service is to increase online marketing and provide education on making brown sugar that is correct and good for health. Brown sugar has its own advantages, but improper processing can harm health in order to gain unilateral benefits. Based on the results of observations when visiting brown sugar craftsmen (partners), information was obtained that the marketing of palm sugar palm sap was carried out online through social media face book and product orders had reached the Pekanbaru area, although not routinely. Therefore community service is carried out by providing outreach to brown sugar craftsmen in order to expand the marketing network which will increase sales, production and profits so as to open jobs for the community. The service method is carried out by observing and interviewing and outreach. It is hoped that the results of PkM activities can increase the knowledge of brown sugar craftsmen about online brown sugar marketing and the quality of brown sugar production and hygiene.